Radiological Features of Changes in the Lungs Caused by Fast- or Slow-Growing Nontuberculous Mycobacteria - R. B. Amansakhedov; L. I. Dmitrieva; T. G. Smirnova; A. A. Veshkin; A. E. Ergeshov (Вестник рентгенологии и радиологии)
Objective: to compare radiological features of pulmonary nontuberculous mycobacterioses (NTM) caused by fast- or slow-growing mycobacteria.Material and methods. Radiological features of the disease were studied in 110 patients with newly diagnosed NTM. The patients were divided into two groups: 70 (63.6%) patients with slow-growing NTM and 40 (36.3%) with fast-growing NTM. The diagnosis was based on patient’s complaints, specified case history, radiological studies, clinical laboratory studies, sputum smear studies, bronchoalveolar lavage studies, different types of bronchial biopsies, and video-assisted thoracoscopic surgery resection samples. According to the results of high-resolution computed tomography (HRCT), a comparative analysis of the degree of involvement in the pathological process of such anatomical formations as parenchyma and stroma, vessels, bronchi, pleura and intrathoracic lymph nodes was carried out.Results. The analysis of HRCT studies showed that fast-growing NTM is not characterized by gross deformation of bronchopulmonary structures. There is a more pronounced infiltrative phase with the involvement of vessels, pleura and bronchial lesions of smaller generations, the formation of broncho-bronchiolectasias and symptoms of bronchiolitis, faster clinical and radiological involution under dynamic observation. Slow-growing NTM is characterized by a more severe deformation of bronchopulmonary structures with the formation of different-sized bronchiectasis, bronchogenic cavities, a more torpid course of the inflammatory process.Conclusion. Despite the similarities of clinical and radiological patterns of NTM, we established some distinguished features for slow-growing and fast-growing types.